PDE escola na dimensão do ensino e aprendizagem no sistema municipal de ensino de Santa Rita/PB - Dantas, Veridiana Xavier (2017)
In this study, we looked at Educational Policies in the macro and micro contexts of these policies in order to analyze the Federal School Development Plan - PDE Escola, in the municipality of Santa Rita/PB. The interest in this subject is justified by our understanding that this program is involved in the development of school management. Thus, we highlight the public policies, especially, PDE Escola. Our general objective was to analyze the effects of the PDE Escola for the development of school management in the criterion of teaching and learning effectiveness of the Municipal Teaching System of Santa Rita/PB. We analyze the local context in the organized and articulated Curriculum categories and Effective Practices within the classroom. The study was carried out in a school that composes said system. The guiding thread to address this theme was focused on Brazilian public policies aimed at improving schools at the municipal level. Our research has emphasized the official documents that govern public educational policies in Brazil, more specifically, in relation to the PDE Escola program. In addition, we refer to the Federal Constitution (CF, 1988), the Law on Guidelines and Bases of National Education (LDBEN Law No. 9.394/1996), National Education Plan Law No. 13,005/2014 (PNE), Municipal Education Plan Law No 1666/2014 (SMEs). In addition, we focus on the data analysis approach in the continuous policy cycle of authors such as Ball, (1989); Ball, Gold and Bowe (1992); Ball, (1994); Ball, Maguire and Braun (2016). To support our methodological choice, we chose (BOGDAN, BIKLEN, 1994), whose assumptions point to the need for qualitative research, in which the direct source of data is the natural environment, the researcher being the main instrument. From this perspective, we conducted a case study supported by the authors Stake (2012) and Yin (2010). The data that constituted the corpus of the research were collected through the application of semi-structured interviews and participant observation. Our initial objectives sought to understand the PDE Escola's process of action in the Dimension of Teaching and Learning; identify the development of the actions targeted by the PDE Escola; to show which elements of the PDE Escola are announced based on the performance of the professionals of the education professionals surveyed; identify in the criterion of school effectiveness teaching and learning. Based on the requirements organized; articulated curriculum and effective practices within the classroom to improve the processes of school management of the Municipal Teaching System of Santa Rita/PB. In the dimension of Teaching and Learning, we conclude that, faced with the actions carried out by the actors involved in the process, there were positive effects, given the discourses of the subjects studied, in these discourses, the most important are financial and pedagogical autonomy, reorganization and application of resources in a correct way and as a negative point, there is an increase in insufficient work and resources, as well as the lack of involvement on the part of some. Therefore, the research revealed, based on the statements analyzed, that school management is democratic and participatory when it comes to the context of results/effects, education professionals are the main actors in this arena of results pressure, since they are the ones who recreate and reinvent politics, in the moments of acting/staging, translation and interpretation.